The “discussion” in the classrooms. A study about citizen training experiences in secondary schools in Córdoba, Argentina (Praxis Educativa, 2021)
This article offers an approach to the citizenship training experiences of young people who attend secondary schools in Argentina. After reviewing and systematizing part of the studies that have focused on issues related to citizenship education, it is based on the relevance of incorporating the analysis of the "discussions" of controversial issues that take place daily in schools. In this sense, an attempt is made to show how the ethnographic approach, which implies the prolonged presence of the researcher in the field, makes it possible to identify and closely monitor the ways in which the relationships between students, teachers and parents are structured. In this way, it is possible to distinguish and analyze a series of processes in which different and unequal ways of constructing citizenship are expressed.